Increased LDH5 expression is associated with lymph node metastasis and outcome in oral squamous cell carcinoma - Grimm, Martin; Alexander, Dorothea; Munz, Adelheid; Hoffmann, Jürgen; Reinert, Siegmar (Clinical & experimental metastasis, 2013)
Oral squamous cell carcinoma (OSCC) account for more than 90 % of all oral malignant lesions. Lactate dehydrogenase 5 (LDH5) has the highest efficiency among all other isoenzymes to catalyse pyruvate transformation to lactate and is significantly overexpressed in several different tumour entities. LDH5 overexpression confers an advantage on malignant cells, allows them to grow faster, and to metastasize. No data regarding LDH5 expression and OSCC outcome are available. Expression of LDH5 was analysed in OSCC specimen (n = 191) and cancer cell lines (BICR3, BICR56) by immunohistochemistry, real-time quantitative reverse transcription-PCR (RT-PCR) analysis, and western blotting. Scanned images were digitally analysed using ImageJ and the immunomembrane plug-in. LDH5 expression on protein level was correlated with clinicopathological characteristics and impact on survival. LDH5 was co-labelled with glucose transporter-1 (GLUT-1), Ki-67, and hypoxia inducible factor 1 (HIF-1α) in immunohistochemical double staining experiments. Expression subgroups were identified by receiver operating characteristics analysis. LDH5 expression was significantly associated with tumour progression, and recurrence of the tumour. Multivariate analysis demonstrated LDH5 expression as an independent prognostic factor (p < 0.0001). Immunohistochemical double staining experiments revealed LDH5 expression by cancer cells in association with glucose uptake (GLUT-1), proliferation (Ki-67), and hypoxia (HIF-1α). LDH5 specificity was confirmed by western blot and RT-PCR analysis. For the first time, this study provides evidence that LDH5 expression in OSCC might be associated with tumour formation and metastasis in a large patient cohort. Therefore, adjuvant therapies targeting glucose metabolism might be promising for therapy of OSCC.